1992
DOI: 10.1007/bf01208726
|View full text |Cite
|
Sign up to set email alerts
|

Preferred ambient temperature for old and young men in summer and winter

Abstract: To investigate the effects of age on thermal sensitivity, preferred ambient temperature (Tpref) was compared between old (71-76 years) and young (21-30 years) groups, each consisting of six male subjects in summer and winter. The air temperature (Ta) was set at either 20 degrees C or 40 degrees C at commencement. The subject was directed to adjust the Ta for 45 min by manipulating a remote control switch to the level at which he felt most comfortable. In the older group, the Tpref was significantly lower in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(61 citation statements)
references
References 7 publications
3
55
1
2
Order By: Relevance
“…Because of sweat production, dehydration typically accompanies heat stress and subsequent increases in body temperature (8,45,68). Notably, mild dehydration (i.e., Յ2% body weight loss) is usually associated with impairments in various aspects of cognitive function, including aspects of attention (5), memory (7,15,20), and executive function (6,7,20).…”
Section: Other Considerationsmentioning
confidence: 99%
“…Because of sweat production, dehydration typically accompanies heat stress and subsequent increases in body temperature (8,45,68). Notably, mild dehydration (i.e., Յ2% body weight loss) is usually associated with impairments in various aspects of cognitive function, including aspects of attention (5), memory (7,15,20), and executive function (6,7,20).…”
Section: Other Considerationsmentioning
confidence: 99%
“…An age-related decline in thermoregulatory sweating further compromises heat loss and increases thermal strain in warm ambient conditions and during exercise. Reduced evaporative heat loss from the skin surface results from a decline in thermoregulatory sweating, due to a decreased thermal sensitivity (32) and atrophy of the sweat glands (17,19), producing a lower sweat output per gland (23,24,39).…”
mentioning
confidence: 99%
“…The elderly who are less cognizant of changes in environmental temperature may fail to make appropriate behavioral modifications to prevent hypothermia. The thermal insensitivity of the elderly has been well documented (Collins et al, 1981;Edholm, 1978;Natsume et al, 1992;Watts, 1971). Cowburn and Fox (1974) observed that older individuals are less able to discriminate between temperature differences than young adults.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is important to investigate comfort zones for the elderly (Collins et al, 1981;Tochihara et al, 1993) as the elderly may be more susceptible to hypothermia during periods of endogenous and/or exogenous thermal stress (Anderson et al, 1996). The reduced thermoregulatory responses and reduced functions of thermal perception in the aged may blunt their thermoregulatory behavior to cold stress, and thus facilitate the onset of hypothermia in daily life (Natsume et al, 1992). In general, it has been considered that the elderly prefer higher indoor temperatures in winter, but this is still controversial.…”
Section: Introductionmentioning
confidence: 99%